'Horrid' and 'infamous' practices: the kidnapping and stripping of children, c.1730–c.1840. Issue 162 (27th December 2018) - Kelly, James
Abstract: Among the abuses experienced by children in Ireland in the eighteenth and nineteenth centuries, kidnapping and stripping stand out both for what they reveal of the changing nature of the manner in which children were preyed upon and contemporary attitudes to children and child welfare. Though it is misleadingly presented as evidence of the existence of a vibrant trade in 'white slaves', children were not only kidnapped so they could be 'sold' in the crown's Caribbean and American colonies. They were also targeted domestically for a variety of pursuits in which children laboured – among which begging and chimney sweeping stand out. In any event, the diminished visibility of child kidnapping after the 1780s suggests it was not pursued actively thereafter. Children continued to be targeted, but the primary object of those who did so was to strip them of the clothes and jewellery they wore in order to realise the monetary value of these goods. Pursued primarily by female offenders, the fact that a majority of the reported incidents occurred in Dublin, Belfast, Limerick and Cork indicates that it was first and foremost an urban crime. Its identification attests both to the vulnerability of children to exploitation, and to the active engagement of adults in that exploitation.